An Education in Sport Competition, communities and identities at the University of Westminster since 1864 - Clapson, Mark (University of Westminster Press, 2013)
"The story of sporting communities and individuals at the University of Westminster over 150 years is the second book to explore the institution's diverse history including its role as a pioneer of women's sports. Drawing upon the University's extensive archives this richly illustrated book celebrates its unique, ground-breaking sports heritage. A print paperback can be purchased direct from the University of Westminster for £20 following this link: www.westminster.ac.uk/historybooks Staff, students and alumni can claim a 20% discount on this price."